(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In today’s world, where everyone has their own technology device, whether it’s a cellphone, an iPad or tablet, or even a laptop and computer, it is evident that everyone can access and watch any video posted or shared on the internet, even violent ones, as we have no control over what other internet users may post and share in the digital world. Social media has no limits; it may or may not benefit the younger generation’s minds. Teenagers’ daily lives today include extensive use of social media, but regrettably, it significantly impacts their values, attitudes, and behaviors. The researchers found out that the majority of the respondents are between the age bracket of eighteen to twenty (18-20) years old with a percentage of eighty-two-point five percent (82.5%), while the highest number of respondents are male with a percentage of seventy- seven (77%). The findings revealed that Facebook is the most frequently used social media platform. At the same time, emotional violence is the most common kind of violent video content that the respondents are exposed to on social media platforms. In behavioral effects of watching violent video content, “I get the urge to do what I just watch online” ranks the highest with a mean of two point sixty-seven (2.67), interpreted as often. While in psychological effects, “I get intrigued and curious about what I just watched online” ranks first with a mean of three-point zero-six (3.06), interpreted as often. Lastly, in psychosocial effects, “I get bored every time I can’t access the internet to watch the latest violent video content” ranks the highest with a mean of two point thirty-three (2.33), interpreted as seldom. Violent video content is all over the internet; whenever we browse, we see it without even looking for it since it just randomly pops up in social media sites’ news feeds. Nowadays, everyone has access to the internet. This means that, despite their resistance or discomfort, they can easily be reached and be influenced by these videos.